2019
DOI: 10.1016/j.trci.2019.09.008
|View full text |Cite
|
Sign up to set email alerts
|

The Brain Health Champion study: Health coaching changes behaviors in patients with cognitive impairment

Abstract: IntroductionConverging evidence suggests that increasing healthy behaviors may slow or prevent cognitive decline.MethodsWe piloted a six-month, randomized, controlled investigation of 40 patients with mild dementia, mild cognitive impairment, or subjective cognitive decline. The intervention consisted of weekly motivational interviewing phone calls and three visits with a “Brain Health Champion” health coach, who guided participants to achieve personalized goals. Changes in behavior were measured using validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 53 publications
4
8
0
Order By: Relevance
“…Practical analyses for required sample size were conducted by examining related HC literature and the samples recruited to demonstrate efficacy therein. Studies examining the efficacy of HC on improving psychological and cognitive variables were conducted with sample sizes ranging from 40 to 45 total participants and demonstrated significant improvement in outcome measures [ 14 , 15 , 18 ]. Taken together, a sample size of at least 100 participants was pursued for this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Practical analyses for required sample size were conducted by examining related HC literature and the samples recruited to demonstrate efficacy therein. Studies examining the efficacy of HC on improving psychological and cognitive variables were conducted with sample sizes ranging from 40 to 45 total participants and demonstrated significant improvement in outcome measures [ 14 , 15 , 18 ]. Taken together, a sample size of at least 100 participants was pursued for this study.…”
Section: Methodsmentioning
confidence: 99%
“…Health coaching (HC) is a guided intervention wherein a health coach assists participants in achieving their desired health-related outcomes through goal-setting, education, motivation, re-assessment, and personalized, guided progression [ 13 ]. In previous studies, HC improved many of the lifestyle factors associated with ADRD [ 14 , 15 ] and may facilitate increased engagement in behaviors believed to benefit cognition [ 15 ]. However, HC’s efficacy for specifically decreasing ADRD risk and improving cognitive-related function among an at-risk sample has not, to our knowledge, yet been examined.…”
Section: Introductionmentioning
confidence: 99%
“…In the Brain Health Champion study, our team demonstrated the efficacy of a low-cost, health-coaching intervention in older adults with MCI or mild dementia. Using evidence-based BCTs, including MI and BA, the health-coaching intervention was associated with increased adherence to brain-healthy behaviors and improved self-reported quality of life [ 559 ]. The results of these studies demonstrate the promise of employing models of evidence-based BCTs to encourage the adoption of brain-healthy behaviors.…”
Section: Promoting Successful Cognitive Agingmentioning
confidence: 99%
“…These seminal findings warrant the search for methods to operationalize this knowledge to clinically promote brain health. The recent Brain Health Champion study demonstrated a motivational-interviewing intervention significantly improving physical activity, adherence to a Mediterranean diet, social/cognitive stimulation, and quality of life in patients with SCD or MCI [58]. Although the study lacked a formal calendar or organizational system, it highlighted the importance of goal setting, which was incorporated into the EMS component of our program.…”
Section: Discussionmentioning
confidence: 99%